P3.172 Prevalence of Genital Infections with Chlamydia Trachomatis (CT), Neisseria Gonorrhoea (NG) and Trichomonas Vaginalis (TV) in Clients of Public HIV Counselling Institutions in North Rhine-Westphalia, Germany: The STI-HIT Study. (13th July 2013) - Bremer, V; Jansen, K; Steffen, G; Sarma, N; Lucht, A; Muenstermann, D; Tiemann, C
Abstract : Background: Chlamydia (CT), gonococci (NG) or trichomonas (TV) infections are not notifiable in Germany. Only few prevalence data exist for the general population. We measured CT, NG and TV prevalence in clients attending local public health authorities (LPHA) offering anonymous HIV tests to evaluate whether these tests should be routinely offered to this population. Methods: LPHA in North Rhine-Westphalia screened clients for genital infections with CT, NG and TV on basis of self-collected vaginal swabs (women) and self-collected urine samples (men), using Transcription-mediated amplification (CT and NG: APTIMA Combo 2 ® ; TV: APTIMA ® Trichomonas vaginalis-Assay). We collected information on sociodemographics, sexual and HIV testing behaviour, as well as clinical symptoms. Results: Between 17.11.2012–05.02.2013, 448 men, 357 women and 4 transgender were enrolled by 18 LPHA. Median age was 30 years. 74.7% were born in Germany. Participants reported a median of 2 sexual partners within last six months. A total of 67.7% had a prior HIV test. Most frequent reasons for HIV test were sexual contact to person with unknown HIV status (57.0%), new partner (28.9%), and sex work (8.7%). Overall, 18.6% had at least one prior STI. Thirty-one (3.8%) persons tested positive for CT, 5 (0.6%) for NG, and 2 (0.2%) for TV; of those 4 NG and 2 TV infections were in sex workers. Prevalence for CT was highest in women (4.5%) and sex workers (5.7%). A total of 18.2% of STI-negative and 23.5% of STI-positive clients had clinical symptoms (p = 0.43). Conclusions: Persons attending LPHA for an HIV test do not seem to be a high risk group for STI. NG and TV prevalence is low in this population, except for sex workers. Routine CT testing should be offered to clients asking for an HIV test, independent of symptoms. Sex workers should also be screened for NG and TV.